2015
DOI: 10.1186/s40199-015-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Artemia salina as a model organism in toxicity assessment of nanoparticles

Abstract: BackgroundBecause of expanding presence of nanomaterials, there has been an increase in the exposure of humans to nanoparticles that is why nanotoxicology studies are important. A number of studies on the effects of nanomatrials in in vitro and in vivo systems have been published. Currently cytotoxicity of different nanoparticles is assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay on different cell lines to determine cell viability, a tedious and expensive method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(133 citation statements)
references
References 48 publications
4
107
0
22
Order By: Relevance
“…The same toxicity studies reported that the A salina lethality assay shows similar results to those found in other biological models 27,48 and can be used to study toxicity. However, the validity of using A salina as a screen has not been fully established for oxime-type compounds, so there may not be a direct correlation of the toxicological or pharmacological effects of oximes among A salina and other species.…”
Section: Discussionsupporting
confidence: 67%
“…The same toxicity studies reported that the A salina lethality assay shows similar results to those found in other biological models 27,48 and can be used to study toxicity. However, the validity of using A salina as a screen has not been fully established for oxime-type compounds, so there may not be a direct correlation of the toxicological or pharmacological effects of oximes among A salina and other species.…”
Section: Discussionsupporting
confidence: 67%
“…The general toxicity of apigenin on A. salina was assessed according to a previous study (Rajabi, Ramazani, Hamidi, & Naji, ). Briefly, A. salina eggs were transferred into a flask containing sodium chloride distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The general toxicity of apigenin on A. salina was assessed according to a previous study (Rajabi, Ramazani, Hamidi, & Naji, 2015). Briefly,…”
Section: A Salina Toxicity Assaymentioning
confidence: 99%
“…The genus Artemia is commonly known as the brine shrimp is a small crustacean, which has a short life cycle and can be studied in large number, a distinct advantage over the vertebrates. It is an important model organism in scientific research, such as toxicological evaluation of nanoparticles 2 , heavy metal 3 , and plant products 4 . It has been established as a safe, practical and economic method to determine the bioactivity of plant constituents, i.e., Brazilian 5 ; Savannah 6 ; Indian 7 ; Sudanese 8 ; and Tanzania 9 medicinal plants.…”
Section: Introductionmentioning
confidence: 99%